Advancements in therapeutics for inborn errors of metabolism. Issue 6 (22nd December 2022) - Turner, Alicia; Glinton, Kevin E.; Sutton, V. Reid
Abstract : Purpose of review: To present new therapeutic modalities for inborn errors of metabolism that are in clinical trials or recently approved by the US Food and Drug Administration (FDA) and to improve pediatricians' understanding of therapies their patients with inborn errors of metabolism receive. Recent findings: New therapies that move beyond the old standard modalities of recombinant human enzyme therapies, diet and medications have been recently approved by the US FDA to include nonhuman enzyme therapies, gene therapy and chaperone therapies. Summary: These new therapies offer more therapeutic options for individuals with inborn errors of metabolism. These new therapies have the potential to improve patient compliance and outcomes. Many other novel modalities are in the development pipeline, and are likely to transform the management of inborn errors of metabolism over the coming decade.